A utilização de experimentos e simulações no ensino de física com o uso do software Tracker com as plataformas PHET e QUIZ - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This study aimed to investigate and analyze the development of kinematics learning process using an educational approach that sought to articulate the operational and pedagogical use of the Software Tracker. So we went to a pedagogical action, which was designed and developed with the students of the 9th grade of elementary school, a state school in the city of Caçapava do Sul - RS. The didactic sequence described herein was based on the theories of David Paul Ausubel (Theory of Meaningful Learning) and Lev Vygotsky Semenovitch (Theory of Cognitive Development). The methodology used in the research was qualitative, observational, participatory research, through the case study. The results suggest that the activities involving experiments and simulations are potentially facilitating the meaningful learning process in teaching physics. Through the students' reports, there was a greater motivation to learn, created by activities such as the use of the Tracker software.
Keywords: Experimento e simulação; Software Tracker; Sequência didática; Ensino de física; Meaningful Learning; Cognitive development; Motivation; Kinematics; Tracker Software; Teaching of physics; Simulations; Cinemática; Motivação; CNPQ::CIENCIAS EXATAS E DA TERRA